Analysis of the influencing factors of delivery timing and mode of preterm maternal in a maternity and child care hospital in Beijing - YUAN Li; REN Hong; CHEN Xiaojin; WANG Huiyu (Yixue xinzhi zazhi, 2024)
Objective To investigate the influencing factors of delivery timing and delivery mode of preterm maternal in a maternity and child care hospital in Beijing.Methods The general clinical data of preterm maternal in the hospital from January 2017 to December 2019 were analyzed retrospectively and divided into the early and mid-preterm group and late preterm group according to the delivery weeks. And were also divided into the natural birth group and cesarean section group according to the delivery mode. Multi-factor Logistic regression was used to analyze the influence factors of delivery timing and delivery mode of maternal in different groups.Results  639 pregnant women (5.42%) had preterm birth, of which 132 cases (20.66%) had early and mid-preterm birth and 507 cases (79.34%) had late preterm birth. 328 cases (51.33%) were delivered by cesarean section and 311 cases (48.67%) were delivered naturally. Age, adverse birth history, scar uterus, folic acid administration during pregnancy and complications of pregnancy were the independent factors of early and mid-preterm. Age, BMI, multiple births, scar uterus and complications of pregnancy were independent factors of cesarean section selection during premature delivery. The 1 min and 10 min Apgar scores of early and mid-preterm infants were significantly lower than those of late preterm infants, and the mortality within 1 year was significantly higher than that of the late preterm infants (P